PERSEPSI PETANI KELAPA SAWIT DARI ASPEK SOSIAL TERHADAP PEMBAKARAN LAHAN(STUDI KASUS DI DESA TANJUNG LEBAN KECAMATAN KUBU KABUPATEN ROKAN HILIR) - Syukri '; Roza Yulida; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Land fires in Rokan Hilir still occur every year, especially during the dry season. Which one of area who fired-prone land is village of TanjungLeban, district of Kubu regency of Rokan Hilir. The purpose of this study was to analyze perception farmers of palm oilof the burning land in of social aspects. This study was conducted in February-August 2015. The results showed fires in district of Kubu mainly caused Social factors: lower of public education, lower of participation by local people to prevent the forest fires, while the indicator of the relationship between citizens, do not be a factor fires in Village of Tanjung Leban district of Kubu. Efforts are being madepublicto prevent fires wason a routine patrol, cleaning ditchesand drainage emains, make dams ditches parent, preparation tools anticipation of fire. Keywords: perception, burning land, farmers